Ruthenium oxide nanostring clusters anchored Graphene oxide nanocomposites for high-performance supercapacitors application. (November 2018) - Kumar, K. Yogesh; Archana, S.; Namitha, R.; Prasanna, B.P.; Sharma, S.C.; Raghu, M.S.
Graphical abstract: Highlights: GO-RuO2 nanocomposites were synthesized by simple hydrothermal method. GO-RuO2 nanocomposites were characterized by XRD, SEM, TEM and EDS. GO-RuO2 nanostring composite has shown a maximum specific capacitance of 859 Fg −1 at the scan rate of 5 mVs −1 . GO-RuO2 nanostring composite electrode exhibits tremendous cyclic stability. Abstract: Here, we report simple hydrothermal method for the preparation of Graphene oxide (GO) is embellished with nanostring clusters of ruthenium oxide (GO-RuO2 ). The structure of the nanocomposite material was ascertained using X-ray diffraction (XRD), Raman spectroscopy, Scanning electron spectroscopy (SEM), Energy dispersive spectroscopy (EDS) and Transmission spectroscopy (TEM). The supercapacitor performance of the nanocomposites was investigated in acidic electrolyte, 1.0 M H2 SO4, in a three-electrode setup. GO-RuO2 nanostring composite has shown a maximum specific capacitance of 859 Fg −1 at the scan rate of 5 mVs −1 using Cyclic voltammetry (CV) and by using Chronopotentiometry (CP) the specific capacitance towered up to 512 Fg −1 at a current density of 2.5 Ag −1 . Further, the material also possesses a high energy density of 246 Wh kg -1 with a maximum power density of 1028 W kg -1 . GO-RuO2 nanostring composite electrode exhibits tremendous cyclic stability with the specific capacitance retention of nearly 99% of the initial capacitance.